The influence of competence and intellectual capital on the performance of SMEs (Case study on culinary SMEs in Arcamanik District) - Nur Hidayati; Ermi Triaji (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2024)
This study aims to examine and analyze the effect of Competence and Intellectual Capital on the Performance of MSMEs in Culinary Sector MSME Actors in Arcamanik District where Micro, Small and Medium Enterprises (MSMEs) are one of the forces for empowering and developing community economic development, which has a significant role to create economic growth and jobs. This study uses descriptive and verification methods with a quantitative approach using census study techniques (census study). The population in this study were 133 UMKM actors in the Culinary Field in Arcamanik District. The analysis used path analysis (Path Analysis) is used to determine how much influence the variable has, either directly or indirectly, on other variables. The results of this study indicate that: (1) Competence has a significant positive effect on MSME performance. (2) Intellectual Capital has a significant positive effect on MSME Performance (3) The total influence of the Competency and Intellectual Capital variables on MSME Performance is indicated by the magnitude of the coefficient of determination r2 = 0.727 or 72.7% while the influence of external variables or errors is 27.3 % Based on the results of the research above, it can be concluded that the model formed is included in the very strong category, so that in this study the Competency and Intellectual Capital variables have a positive and significant effect and have a very close and difficult link to the Performance of MSMEs in the Culinary Field of Arcamanik District